Mempertahankan Ekonomi Di Masa Pandemi Covid-19 Melalui Kreatifitas Industri Rumah Tangga - Elisa Nurazizah; Dadang Kuswana; Asep Shodiqin (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
This paper aims to determine the socio-economic conditions of the home industry before and after the Covid-19 pandemic and to find out what creativity is done by the home industry in maintaining the economy during the Covid-19 pandemic. This study uses a descriptive method with a qualitative approach. The data collection process was carried out through interviews, documentation and direct observations of the authors in the field. From this research, it was found that there are several ways that the home industry players can use to maintain the economy during the pandemic. Among them is the creativity that is owned will make the resulting product to be different and have its own characteristics. And use social media as a forum to promote the products produced by each of these home industries.